Společná zahraniční a bezpečnostní politika Evropské unie – místo přeludu konečně skutečnost? (Czech Journal of International Relations, 2001)
Simon Duke /ed./: Between Vision and Reality. CFSP's Progress on the Path to Maturity. 1st ed. Maastricht: European Institute of Public Administration, 2000, 319 stran, ISBN 90-6779-145-8.